1990
DOI: 10.1111/j.1399-0004.1990.tb03585.x
|View full text |Cite
|
Sign up to set email alerts
|

The wrinkly skin syndrome: a report of a case and review of the literature

Abstract: A 2 1/2‐year‐old boy born of Jewish Moroccan parents is reported with physical findings of wrinkled skin on the dorsum of the hands and feet, with poor skin elasticity, syndactyly, mild kyphosis and poor muscle tone, the diagnosis being the wrinkly skin syndrome. All reported cases of this heritable disorder of connective tissue are reviewed and discussed in terms of genetics, ethnic clustering and differential diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…The WSS patients had clinical features similar to those described in previous reports [Gazit et al, 1973;Karrar et al, 1983;Casamassima et al, 1987;Hurvitz et al, 1990;Morava et al, 2005] and their phenotype resembled closely the one described for autosomal recessive CLGDD/ARCL type II [Agha et al, 1978;Philip, 1978;Ogur et al, 1990;Kreuz and Wittwer, 1993;Imaizumi et al, 1994;Loeys et al, 2002]. Ogur et al [1990] reported Turkish sibs where the boy was severely affected with the classical form of CLGDD, while his sister showed improvement with age and at the age of 6.5 years presented with a relatively mild disease, including cutaneous manifestations similar to those found in WSS.…”
Section: Discussionsupporting
confidence: 71%
“…The WSS patients had clinical features similar to those described in previous reports [Gazit et al, 1973;Karrar et al, 1983;Casamassima et al, 1987;Hurvitz et al, 1990;Morava et al, 2005] and their phenotype resembled closely the one described for autosomal recessive CLGDD/ARCL type II [Agha et al, 1978;Philip, 1978;Ogur et al, 1990;Kreuz and Wittwer, 1993;Imaizumi et al, 1994;Loeys et al, 2002]. Ogur et al [1990] reported Turkish sibs where the boy was severely affected with the classical form of CLGDD, while his sister showed improvement with age and at the age of 6.5 years presented with a relatively mild disease, including cutaneous manifestations similar to those found in WSS.…”
Section: Discussionsupporting
confidence: 71%
“…Gazit et al (14) coined the term WSS to describe congenital wrinkly skin, more prominent on the dorsae of the hands, the feet, and abdomen, prenatal and postnatal growth retardation hypermobility of joints, increased numbers of creases on palms and soles, and a prominent venous pattern. Subsequently, many patients with additional features were described (13–22). Al‐Gazali et al (11) reported five patients who had overlapping features of GO and WSS.…”
Section: Discussionmentioning
confidence: 99%
“…Wrinkly skin syndrome (WSS; OMIM 278250) is another rare autosomal recessive condition that is characterized by congenital wrinkly skin, prominent venous texture, intrauterine growth retardation, developmental delay, an aged appearance, and various craniofacial and musculoskeletal abnormalities. Since first being described in 1973, around 22 patients have subsequently been reported in the literature (13–22). The occurrences of GO and WSS have been described in different races, but most of the reports are from the countries of the Middle East (8,10,11,14,16,23) and this is linked to the high incidence of consanguineous marriages in this region.…”
mentioning
confidence: 99%
“…Although there are several genes that have been identified as causative for these diseases, only the wrinkly skin syndrome form of cutis laxa (Hurvitz et al, 1990;Zlotogora, 1999) and Ehlers-Danlos forms I, II, and IV (De Paepe and Malfait, 2004) have been linked to mutations in genes for which the mouse orthologs reside in the identified Sagg interval on the proximal arm of mouse chromosome 1 (Nolan et al, 2000).…”
Section: Introductionmentioning
confidence: 99%